Changes of values parents' scholarship in physical culture under the influence of realization set of activities on optimization of physical education of elder preschoolers - O.A. Tomenko; A.U. Starchenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to consider results of values of parents' scholarship in physical training, also degree of its changes, originated under influence of set of activities on optimization physical education of elder preschoolers. Material: 117 parents took place in experiment, children of those were in control and experimental groups. Results: for improving level of theoretical and practical readiness of parents in the issues of physical education there were conducted different forms of work and developed methodical recommendations. It is found out that values of parents' physical scholarship of experimental group improved by 38% as compared to the beginning of research. C onclusions: under influence of set of activities on optimization of physical scholarship of elder preschoolers there were marked increase of parents' scholarship in physical training that allows to recommend its use in preschool institutions.